Profil Sosiodemografi Wanita Hamil dengan Infeksi Saluran Kemih: Sebuah Tinjauan Sistematis dari Penelitian Saat Ini: Analisis - Fitriyadi Kusuma; Kemal Akbar Suryoadji; Adib Kamil Putra Kadarusman; Geraldus Sigap Gung Binathara; Salsa Billa As’syifa; Surahman Hakim (PT Kalbe Farma Tbk., 2025)
Introduction: Untreated UTIs during pregnancy can lead to complications for both the mother and the fetus, highlighting the importance of appropriate management. Understanding the sociodemographic profiles of pregnant women with UTIs can aid in tailored interventions and care. Methods: This systematic review followed a protocol registered in the International Prospective Register of Systematic Reviews (PROSPERO ID: CRD42024507145). Cohort cross-sectional studies focusing on the sociodemographic profiles of pregnant women with UTI were systematically searched and selected from databases such as ScienceDirect, Cochrane, Scopus, and PubMed. Eligibility criteria included relevance to sociodemographic profiles, clear extraction and statistical analysis methods, and publication in English. Data extraction and study selection were conducted independently by six researchers, with any discrepancies resolved through discussion. Results: Three studies met the inclusion criteria and were included in the systematic review. The studies conducted in the United States, Cameroon, and Bangladesh, which included 46,398 pregnant women, revealed diverse sociodemographic factors associated with UTI risk among pregnant women. Factors such as low educational attainment, low household income, and racial/ethnic disparities were identified as significant contributors to UTI prevalence in the United States. In Cameroon, although a high UTI prevalence was observed, no significant risk factors were identified. In Bangladesh, maternal undernutrition, primiparity, and low paternal education were significant risk factors for UTIs among pregnant women. Antibiotic sensitivity was varied, indicating the complexity of UTI management. Conclusion: The systematic review emphasizes the importance of considering sociodemographic factors in understanding and addressing UTI risk among pregnant women. Socioeconomic status, cultural disparities, and health-related factors play significant roles in UTI prevalence and management. An intervention to target specific sociodemographic characteristics may be necessary to effectively prevent and manage UTIs in pregnant women across different geographical and socioeconomic contexts.